Temporal analysis reveals a key role for VTE5 in vitamin E biosynthesis in olive fruit during on-tree development - Georgiadou, Egli C.; Ntourou, Thessaloniki; Goulas, Vlasios; Manganaris, George A.; Kalaitzis, Panagiotis; Fotopoulos, Vasileios (Frontiers in Plant Science, 2015)
The aim of this work was to generate a high resolution temporal mapping of the biosynthetic pathway of vitamin E in olive fruit (Olea europaea cv. ‘Koroneiki’) during seventeen successive on-tree developmental stages. Fruit material was collected from the middle of June until the end of January, corresponding to 6-38 weeks after flowering (WAF). Results revealed a variable gene regulation pattern among 6-38 WAF studied and more pronounced levels of differential regulation of gene expression for the first and intermediate genes in the biosynthetic pathway (VTE5, geranylgeranyl reductase, HPPD, VTE2, HGGT and VTE3) compared with the downstream components of the pathway (VTE1 and VTE4). Notably, expression of HGGT and VTE2 genes were significantly suppressed throughout the developmental stages examined. Metabolite analysis indicated that the first and intermediate stages of development (6-22 WAF) have higher concentrations of tocochromanols compared with the last on-tree stages (starting from 24 WAF onwards). The concentration of α-tocopherol (16.150-32.454 mg/100g F.W.) were substantially greater (up to 100-fold) than those of β-, γ- and δ-tocopherols (0.129-0.246 mg/100g F.W., 0.134-0.334 mg/100g F.W., 0.136-0.277 mg/100g F.W., respectively). In regard with tocotrienol content, only γ-tocotrienol was detected. Overall, olive fruits (cv. ‘Koroneiki’) exhibited higher concentrations of vitamin E until 22 WAF as compared with later WAF, concomitant with the expression profile of phytol kinase (VTE5), which could be used as a marker gene due to its importance in the biosynthesis of vitamin E. To the best of our knowledge, this is the first study that explores the complete biosynthetic pathway of vitamin E in a fruit tree crop of great horticultural importance such as olive, linking molecular gene expression analysis with analytical tocochromanol content.